Crisis Management in Socio-Economic Systems in the Context of Digitalization Using the Example of a “Smart City” - V. K. Sarian; R. Yu. Umanskiy (Мир новой экономики, 2024)
The purpose of this study is to analyze the processes of transformation of crisis management in socio-economic systems in the context of digitalization and to develop, using the example of a “Smart City”, an approach to the formation of a crisis management system using modern digital technologies and embedding in this system a controlling module responsible for information and analytical support of decision-making processes.   The research methodology uses a systematic, complex and logical analysis of the ongoing processes of digitalization, as well as a theoretical and methodological apparatus for developing a crisis management system in socio-economic systems in the context of digitalization using the example of a “Smart City”.   The results of the study include the following: an approach to the transformation of crisis management in socio-economic systems in the context of digitalization has been developed using the example of a “Smart City”; the main requirements and provisions for the formation of a crisis management system in the conditions of digitalization have been formulated; based on the analysis, comprehensive proposals for the formation of a crisis management system using the example of a “Smart City” have been formulated with a built-in controlling module.